2020
DOI: 10.37394/23207.2020.17.93
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Banks Profitability: Domestic and Foreign Comparison

Abstract: Attempt at analyzing banks profitability informed this study. For sound and robust reviews of end report, the study took at comparing commercial banks across countries in Africa with emphasis on Nigeria, Ghana and South Africa owing to presumed position they occupy in the continent. To achieve its aims and from data provided by World Bank Group – International Monetary Funds, the study mirrored commercial banks profitability with total income (TI) hence, the dependent variable. The independent variables were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Hence, a proportion increase in total savings to gross domestic product brings about a corresponding increase in human development indicator. Total savings contribution to gross domestic product could be regarded as a significant determinant of economic development in the short run, which is similar to findings by Babajide, Okunlola, Adedoyin, Okafor, and Isibor (2020c); Adeleye et al (2018); and Babajide (2012).…”
Section: Estimated Long-run Coefficientssupporting
confidence: 85%
“…Hence, a proportion increase in total savings to gross domestic product brings about a corresponding increase in human development indicator. Total savings contribution to gross domestic product could be regarded as a significant determinant of economic development in the short run, which is similar to findings by Babajide, Okunlola, Adedoyin, Okafor, and Isibor (2020c); Adeleye et al (2018); and Babajide (2012).…”
Section: Estimated Long-run Coefficientssupporting
confidence: 85%
“…Whereas, Model 4, indicated that FII is not statistically significant in explaining GDP. However, the pitfalls inherent in PFE models, which [62,64,65] pointed out in their studies, informed taking a further examination of the significance of the variable by employing the randomization impacts using the PRE. Thus, what the PRE does is consider the heterogeneity, time-invariant, and individual country effect by allowing for the control of unseen heterogeneity through the general least squared method (GLS), where the error terms of observations are randomly distributed.…”
Section: Visual Trendmentioning
confidence: 99%
“…Scanty literature between business sustainability and ecommerce in Nigeria exit. More so, the adoption of the concept is barely new and because of the nature of variables often generated, it makes empirical insight tasking than the mostly exploratory and case study approach often conducted by most researchers Saraswati et al (2022), Okunlola et al (2020), Babajide et al (2020b), Olah et al (2018); Jere et al (2014), Ayalew et al (2010).…”
Section: Some Empirical Reviewmentioning
confidence: 99%
“…As such, business has experienced oscillatory trends overtime in growth, expansion and sustainability at every stage introduction of a new technological innovation. In fact, it is recorded that barely five percent of companies rarely survive the first five years of its establishment (Okunlola et al, 2020a;Babajide et al, 2020).…”
Section: Introductionmentioning
confidence: 99%